Targeting Toxoplasma gondii CPSF3 as a new approach to control toxoplasmosis - Andrés Palencia; Alexandre Bougdour; Marie‐Pierre Brenier‐Pinchart; Bastien Touquet; Rose‐Laurence Bertini; Cristina Sensi; Gabrielle Gay; Julien Vollaire; Véronique Josserand; Eric Easom; Yvonne R Freund; Hervé Pelloux; et al. (EMBO Molecular Medicine)
Abstract Toxoplasma gondii is an important food and waterborne pathogen causing toxoplasmosis, a potentially severe disease in immunocompromised or congenitally infected humans. Available therapeutic agents are limited by suboptimal efficacy and frequent side effects that can lead to treatment discontinuation. Here we report that the benzoxaborole AN3661 had potent in vitro activity against T. gondii. Parasites selected to be resistant to AN3661 had mutations in TgCPSF3, which encodes a homologue of cleavage and polyadenylation specificity factor subunit 3 (CPSF‐73 or CPSF3), an endonuclease involved in mRNA processing in eukaryotes. Point mutations in TgCPSF3 introduced into wild‐type parasites using the CRISPR/Cas9 system recapitulated the resistance phenotype. Importantly, mice infected with T. gondii and treated orally with AN3661 did not develop any apparent illness, while untreated controls had lethal infections. Therefore, TgCPSF3 is a promising novel target of T. gondii that provides an opportunity for the development of anti‐parasitic drugs.